Zimbabwe's economic crisis hits sugar refining - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
Zimbabwe's principal sugar refiner ZSR stopped production in June 2002 as a...